Molecular phylogeny of the subgenus Syrrhophus (Amphibia: Anura: Eleutherodactylidae), with the description of a new species from Eastern Mexico. Issue 1 (31st December 2022) - Hernández-Austria, Raquel; García-Vázquez, Uri O.; Grünwald, Christoph I.; Parra-Olea, Gabriela
Abstract : The Eleutherodactylus subgenus Syrrhophus has a complex taxonomic history. For many years the species were classified into series and groups of species based on morphological and allozyme data. However, most of the species have conservative morphology, and their phylogenetic relationships have not been resolved. Furthermore, recent studies employing molecular tools have shown that Syrrhophus diversity is highly underestimated. Here, we present a near-complete phylogenetic hypothesis based on mitochondrial data (16S rRNA, cytochrome c oxidase subunit I, and cytochrome b) and employing maximum likelihood and Bayesian methods. The Bayesian tree has high support values (posterior probabilities ≥0.95) whereas the maximum likelihood hypothesis has generally low values (bootstrap support <70). Both phylogenetic analyses recovered Syrrhophus as monophyletic and composed of four main, allopatric clades ( E . symingtoni clade, E . longipes clade, E . modestus clade, and E . nitidus clade) concordant with geography. Based on the molecular and morphological data, we describe a new species from the state of San Luis Potosí, Mexico. The new species is most closely related to E . campi and E . cystignathoides from which it has a genetic distance >7% in 16S rRNA. Finally, based on the phylogenetic results, we resurrect E . rubrimaculatus from synonymy. Our results increase the number of species in the subgenus Syrrhophus to 41. We highlight the importance of efforts to study this important component of Mexican biodiversity. http://zoobank.org/urn:lsid:zoobank.org:pub:3C2B2315-D5C8-420A-938C-A2B3A75B4248